Direction of commissural axon projections in different regions of the spinal cord during chicken embryonic development. (1st September 2017) - Li, Han; Yang, Ciqing; Yusoff, Narazah Mohd; Yahaya, Badrul Hisham; Lin, Juntang
Graphical abstract: In the five investigated regions (cervical region, anterior limb, anterior thorax, posterior thorax, and posterior limb), most axons projected rostrally after crossing the floor plate while a minority projected caudally. The ratio of rostral and caudal projections was significantly different between the five investigated regions, except between the cervical region and the anterior limb. A–E shows the GFP-positive areas in the cervical region, anterior limb, anterior thorax, posterior thorax, and posterior limb, respectively. A1–E1 shows the axon projection results generated using the open-book procedure from A–E, respectively. F displays transverse view and open-book view of the spinal cord. Abbreviations: AL, anterior limb; AT, anterior thorax; C, caudal; CR, cervical region; FP, floor plate; GFP, green fluorescence protein; ILC, intermediate longitudinal commissural; MLC, medial longitudinal commissural; PL, posterior limb; PT, posterior thorax; R, rostral; RP, roof plate. Scale bars = 1 mm in A, also for B–E; 50 μm in A1, also for B1–E1. Highlights: Electroporation and open-book time points are important to investigate axon projection. Plasmids' expression can be limited to very specific spinal cord regions. There are significant difference between RQ and CQ in different spinal cord regions. The ratio of RQ/CQ is different among investigated spinal cord regions. PL and AT are the most likely to project rostrally and caudally, respectively. Abstract: Few researchers have investigated the direction of commissural axon projections on the contralateral side of the vertebrate embryonic spinal cord, especially for comparison between its different regions. In this study, pCAGGS-GFP plasmid expression was limited to different regions of the chicken embryonic spinal cord (cervical, anterior limb, anterior thorax, posterior thorax and posterior limb) at E3 using in ovo electroporation with modified electrodes and optimal electroporation conditions. Then open-book technique was performed at E6 to analyze the direction of axon projections in different spinal cord regions. The results show that in the five investigated regions, most axons projected rostrally after crossing the floor plate while a minority projected caudally. And there was a significant difference between the rostral and caudal projection quantities ( P  < 0.01). The ratio of rostral and caudal projections was significantly different between the five investigated regions ( P  < 0.05), except between the cervical region and the anterior limb ( P  > 0.05). The projections were most likely to be rostral for the posterior limb followed by the posterior thorax, cervical region, anterior limb and anterior thorax. Our data for the direction of the commissural axon projections will be helpful in the future analyses of axon projection mechanisms and spinal cord-brain circuit formation.